Incidencias de las medidas tributarias y financieras en las micro empresas del sector hotelero en el departamento del Magdalena en tiempos de covid durante el año 2020 - Ortiz Damian, Abdwar Hernan; Cala Morales, Deisy Johana; Tole Escobar, Luisa Fernanda (Universidad Antonio Nariño, 2022)
This research proposal shows the incidents and a detailed analysis of taxes and financial measures of the hotel sector in the Department of Magdalena during Covid in 2020, which were proposed by the National Government to alleviate the crisis. On the other hand, the economic problems generated in micro-enterprises due to quarantines and mobility restrictions are identified. Also, a mixed investigation is carried out, supported by a survey applied to 60 hotels 14 in Magdalena, an interview to find out the professional opinion of a Hospitality and Tourism Administrator. The investigation delivers as a product an instructive booklet with the current tax and financial measures that informs the basic procedures for micro-enterprises in the hotel sector in Magdalena department